Three new tetranuclear phenoxy-bridged metal(II) complexes: Synthesis, structural variation, cryomagnetic properties, DFT study and antiprolifirative properties. (15th March 2019) - Patel, S.K.; Patel, R.N.; Singh, Y.; Singh, Y.P.; Kumhar, D.; Jadeja, R.N.; Roy, H.; Patel, A.K.; Patel, N.; Patel, N.; Banerjee, A.; Choquesillo-Lazarte, D.; et al.
Graphical abstract: Three tetranuclear phenoxy-bridged copper(II) and zinc(II) complexes containing acetic acid (2-hydroxy-3-methoxy-benzylidene)-hydrazide (HL) of formulae [Cu4 (HL)4 ]·4ClO4 ·2H2 O1, [Cu4 (L)4 ]·4H2 O2 and [Zn4 (L)4 ]·4H2 O3 are synthesized and characterized using various physico-chemical methods. The inhibitory effects of the complexes on cell population growth on IMR 32 (neuroblastoma), MCF 7 (breast cancer), HepG2 (hepatocellular carcinoma), L132 (lung cells) cell lines were determined by MTT assay. Abstract: Three tetranuclear phenoxy-bridged copper(II) and zinc(II) complexes containing acetic acid (2-hydroxy-3-methoxy-benzylidene)-hydrazide (HL) of formulae [Cu4 (HL)4 ]·4ClO4 ·2H2 O1, [Cu4 (L)4 ]·4H2 O2 and [Zn4 (L)4 ]·4H2 O3 are synthesized and characterized using various physico-chemical methods. Their X-ray structures reveal that copper(II) complexes1 and2 contain distorted Cu4 O4 cubane core of 4 + 2 type. Zinc complex3 is open cubane like Zn4 O4 core frame work. The coordination sphere in copper(II) complexes1 and2 can be described as a distorted octahedral geometry whereas zinc(II) complex3 has distorted square pyramidal geometry. The variable temperature magnetic susceptibility measurements on tetranuclear cubane like copper(II) complexes in the range 2–300 K indicate antiferromagnetic exchange coupling between copper(II) centers. The best fit data gave J 1 = −82.4 (4) cm −1, J 2 = 22 (2) cm −1 and g = 1.95 (1) ( R 2 = 0.99996) whereas for2 it gave J 1 = −86 (1) cm −1, J 2 = 5 (2) cm −1 and g = 2.074 (7) ( R 2 = 0.9998). The nature of super exchange pathway in copper(II) complexes (1 and2 ) is discussed on the basis of structural, magnetic and molecular orbital considerations. DFT calculations are performed in order to obtain their molecular orbitals and energies using their crystallographic parameters. The inhibitory effects of the complexes on cell population growth on IMR 32 (neuroblastoma), MCF 7 (breast cancer), HepG2 (hepatocellular carcinoma), L132 (lung cells) cell lines were determined by MTT assay. The complex [Cu4 (L)4 ]·4H2 O2 showed a significant anti-proliferative effect. The expression levels of Bax (pro-apoptotic), Bcl2 (anti-apoptotic), Caspase 9 and p53 genes were also studied, wherein genes of interest showed moderate down regulation after treatment with all the complexes.